Why do delays to diagnosis and treatment of lung cancer occur? A mixed methods study of insights from Australian clinicians. Issue 2 (16th April 2020) - Malalasekera, Ashanya; Dhillon, Haryana M.; Shunmugasundaram, Chindhu; Blinman, Prunella L.; Kao, Steven C.; Vardy, Janette L.
Abstract: Aims: Delays in lung cancer diagnosis and treatment can impact survival. We explored reasons for delays experienced by patients with lung cancer to identify themes and strategies for improvement. Methods: We used national timeframe recommendations and standardized definitions to identify General Practitioners and specialists caring for 34 patients who experienced delays in our previous Medicare data linkage study. Clinicians participated in a survey and interview, including qualitative (exploratory, open‐ended questions) and quantitative (rating scales) components. Exploratory content analysis, cross‐case triangulation, and descriptive statistics were performed. Krippendorff's coefficient was used to assess level of agreement between clinicians and patients, and among clinicians, on perceived delays. Results: Overall, 27 out of 50 (54%) eligible clinicians participated (including 11 respiratory physicians and seven medical oncologists). Dominant themes for perceived causes of delay included referral barriers, limited General Practitioner (GP) awareness of subtle clinical presentations, insufficient radiology interpretation, and lack of cancer coordinators. "Unavoidable" delays may occur due to clinical circumstances. Awareness and uptake of referral and timeframe guidelines were low, with clinicians using professional networks over guidelines. There was no consistent agreement on perceived delays between patients and clinicians, and among clinicians (Krippendorff's coefficient .03 [ P = .8]). Conclusions: Strategies for minimizing avoidable delays include efficient GP to specialist referral and more lung cancer coordinators to assist with patient expectations and waitlist management. Clinicians' reliance on experience, rather than guidelines, indicates need to review guideline utility. Raising awareness of benchmarks and unavoidable barriers may recalibrate perceptions of "delays" to diagnosis and treatment of lung cancer.